Executive function and theory of mind as predictors of socially withdrawn behavior in institutionalized children. Issue 1 (30th June 2017) - Selcuk, Bilge; Yavuz, H. Melis; Etel, Evren; Harma, Mehmet; Ruffman, Ted
Abstract: False‐belief understanding and executive functions are two main sociocognitive abilities reliably linked to child social competence. Although institution‐reared children are especially at risk for behavioral problems and cognitive delays, the role that executive function and false‐belief understanding might play in the social withdrawal of institutionalized children has not been examined. The current study used two‐wave data to investigate the concurrent and longitudinal relations of social withdrawal with executive function and false‐belief understanding in institutionalized children; it also allowed investigation of the directionality between executive function and false‐belief understanding. Data were collected from 66 Turkish children (T1 M = 57.83 months, SD = 9.20; T2 M = 69.58 months, SD = 8.45) residing in institutions, at two time points, approximately 1 year apart. We measured false‐belief understanding and executive function via individual assessments, and social withdrawal via care provider reports at both time points. Results showed that both executive function and false‐belief understanding increased between T1 and T2, while social withdrawal did not show a significant change. Path analysis revealed that when T1 age and language were controlled, T1 executive function predicted T2 executive function, and in turn, T2 executive function predicted lessened social withdrawal at T2. In addition, T1 executive function predicted T2 false‐belief understanding. T1 false‐belief understanding was not related to T2 false‐belief understanding, executive function, or social withdrawal. Findings suggested that executive function is an important predictor of social withdrawal in high‐risk populations.